Promosi Kesehatan: Pengenalan Telemedicine Pada Orang Tua Siswa di TK-Al Islam 5 Grobagan - Anggie Annisa Permatasari; Oriza Dwi Satifa; Anisa Setya Ramadhani (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Telemedicine is the provision of long-distance health services by health professionals using information and communication technology, including the exchange of information on diagnosis, treatment, disease and injury prevention, research and evaluation, and continuing education of health service providers for the benefit of improving individual and community health. Health Service Facilities, hereinafter referred to as Health Facilities, are tools and/or places used to provide promotive, preventive, curative and rehabilitative health service efforts carried out by the central government, regional government and/or the community. Health Facilities that provide consultations are health facilities that receive requests and provide Telemedicine consultation services. Health Facilities Requesting Consultation are Health Facilities that send requests for Telemedicine consultations (1). In the partner environment, not many people know about the term telemedicine and the majority have never used these facilities for their daily needs. Therefore, the author wants to hold outreach as part of a health promotion program regarding the introduction of telemedicine to parents of students at TK-Al Islam 5 Grobagan. The aim of this community service is to increase knowledge, provide education, and increase understanding among the community, especially parents of students at TK-Al Islam 5 regarding telemedicine in Indonesia. The output target to be achieved in this community service is the publication of journal articles.